Content Analysis of Flavonoids in the Stems and Roots of Acanthopanax Species in Different Countries - Min Lee, Jeong; Gu Lee, Dong; Kim, Jongkee; Lee, Sanghyun (Asian Journal of Chemistry, 2014)
Content analysis of flavonoids in the stems and roots of Acanthopanax species (A. divaricatus, A. koreanum, A. senticosus and A. sessiliflorus) in different nations was conducted by high performance liquid chromatography. In the stems and roots of Acanthopanax species, the contents of rutin, hyperin, afzelin, quercetin and kaempferol were 0.024-0.326 and 0.059-0.531, 0.391-4.256 and 0.957-3.517, 0.935-10.572 and 1.019-1.185, 0.375-0.885 and 0.394-0.501, 0.193-0.872 and 0.179-0.500 mg/g, respectively. Total content of flavonoids in the stems and roots was highest in A. senticosus (Mt. Baekdu) and A. sessiliflorus (Gongju), respectively. Also, hyperin and afzelin were the most abundant compounds in the roots and stems of Acanthopanax species, respectively. This result will provide useful information in the application of these flavonoids from Acanthopanax species in the nutraceutical, pharmaceutical and cosmeceutical areas.